The added value of a face-to-face pan-European course—what makes it worth it? - de Leeuw, Robert; Huirne, Judith A. F.; Rositto, Christiano; Mabrouk, Mohammed; Barri, Pierre; Bongers, Marlies; Thurkow, Andreas; El-Balat, Ahmed; Vlahos, Nikon; Brolmann, Hans (Frontiers in Medicine, 2024)
Over the past decade, digital education has seen widespread adoption, particularly accentuated during the COVID-19 pandemic. The post-COVID era has further emphasized the advantages of digital education in terms of cost, availability, and sustainability. However, concerns regarding the efficacy of digital education, particularly in skills-based learning and the absence of social interaction, have been raised. This paper will look at the added value of international, face-to-face, skills-based courses.This study evaluates the potential added value of face-to-face international skills courses using the European "Gynecology Experts Training for Upcoming Professionals" (GET-UP) course. Focus group discussions were conducted with participants and faculty members to explore beliefs, attitudes, and perceptions regarding face-to-face learning. Qualitative analysis was performed using thematic analysis to identify domains of added value.The GET-UP course, conducted over four days with a diverse European faculty and participants, highlighted several added-value domains. Themes including diversity, role models, preparation, live interaction, and community emerged from the analysis, emphasizing the significance of face-to-face interaction in enriching the learning experience beyond attaining learning goals.The study underscores the importance of face-to-face interaction in educational settings, offering insights into diverse teaching methods, role modelling opportunities, enhanced preparation, live interactions, and fostering a sense of community. While digital education continues to evolve with interactive features, this study suggests that the inherent pressure and dynamics of face-to-face learning provide unique benefits that may not be easily replicated in digital environments. Future research should investigate and validate these findings further to inform educational practices effectively.